Financial disruptions and bank productivity growth: evidence from the Malaysian experience - Sufian, Fadzlan (Taylor & Francis, 2009)
This paper examines, for the first time, the productivity of the Malaysian banking sector around the Asian financial crisis 1997. The non-parametric Malmquist Productivity Index (MPI) is used to compute individual banks’ productivity levels. We find that the Malaysian banking sector has exhibited productivity regress due to the decline in efficiency. The results seem to suggest that the domestic banks have exhibited productivity progress attributed to technological change, while the foreign banks have exhibited productivity regress due to efficiency decline. We find that the large banks tend to experience productivity growth attributed to technological progress, while the small banks tend to experience productivity decline due to technological regress. The empirical results suggest that the small banks with its limited capabilities are at a disadvantage compared with their larger counterparts in terms of technological advancements, thus, rejecting the divisibility theory.